The Impact Of Organizational Culture On Job Satisfaction Among The Police Officers In Palestine – West Bank - Taysir. Y. D. Ostaali; Khairunneezam Mohd Noor; Kalsom Ali (WorldConferences.net, 2024)
Non-Indexed Publication